2012
DOI: 10.1007/s12640-012-9333-8
|View full text |Cite
|
Sign up to set email alerts
|

Response of Hippocampal Neurons and Glial Cells to Alternating Magnetic Field in Gerbils Submitted to Global Cerebral Ischemia

Abstract: The purpose of this study was to determine whether exposure to an extremely low-frequency magnetic field (ELF-MF, 50 Hz) affects the outcome of postischemic damage in the hippocampus of Mongolian gerbils. After 10-min bilateral carotid occlusion, the gerbils were continuously exposed to ELF-MF (average magnetic induction at the center of the cage was 0.5 mT) for 7 days. The impact of ELF-MF was estimated immediately (the 7th day after reperfusion) and 7 days after cessation of exposure (the 14th day after repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 51 publications
2
37
0
Order By: Relevance
“…The animals were exposed to an ELF magnetic field (50 Hz, average magnetic field of 0.5 mT) for 7 days and/or global cerebral ischemia for 10 min. This study is a continuation of previous research [Rauš et al, ; Rauš Balind et al, ] and provides further insight into the effects of an ELF magnetic field immediately and 1 week after cessation of exposure and global cerebral ischemia at different time points after reperfusion. These studies contribute not only to detecting biological effects of the applied ELF magnetic field, as an external stressor but also in assessing the consequences of such exposure on recovery following global cerebral ischemia in gerbils.…”
Section: Introductionsupporting
confidence: 70%
“…The animals were exposed to an ELF magnetic field (50 Hz, average magnetic field of 0.5 mT) for 7 days and/or global cerebral ischemia for 10 min. This study is a continuation of previous research [Rauš et al, ; Rauš Balind et al, ] and provides further insight into the effects of an ELF magnetic field immediately and 1 week after cessation of exposure and global cerebral ischemia at different time points after reperfusion. These studies contribute not only to detecting biological effects of the applied ELF magnetic field, as an external stressor but also in assessing the consequences of such exposure on recovery following global cerebral ischemia in gerbils.…”
Section: Introductionsupporting
confidence: 70%
“…In this study we applied ELF-MF (50 Hz, 0.5 mT) for 7 days in gerbils submitted to 10-min global cerebral ischemia and measured oxidative stress parameters in distinct brain structures (forebrain cortex, striatum and hippocampus) on the 7 th (immediate effect of ELF-MF) and 14 th day after reperfusion (delayed effect of ELF-MF). These results are part of our comprehensive investigations concerning the effects of ELF-MF in animals with experimentally induced cerebral ischemia [19], [20] and contribute to the explanation of spatial and temporal patterns of oxidative stress in the brain of these animals.…”
Section: Introductionmentioning
confidence: 75%
“…Tissue GFAP-ir expression in sham-operated animals contrasted by a uniform expression within the CA1 with thin and long processes of the labeled astrocytes. Noteworthy, time-dependent alterations of glial cell and cytokine expression following ischemia has been proposed: an initial glial activation phase rapidly occurring within 48 h of the ischemic insult and a delayed phase coincidental with neuronal death occurring over a period of several days postischemia (Yasuda et al, 2011) and under some circumstances, astrocyte proliferation has been observed concurrent with neuronal protection and improved post-ischemic recovery (Raus et al, 2013).…”
Section: Bres : 44116mentioning
confidence: 99%